Application of Optical Floating Zone Method to Dissolution Kinetics of Inclusions in a Steelmaking Slag. Issue 1 (24th September 2018) - Sharma, Mukesh; Dabkowska, Hanna A.; Dogan, Neslihan
Abstract : The dissolution kinetics of micro‐particles (inclusions) in steelmaking slags is investigated using the high temperature confocal scanning laser microscope (HT ‐ CSLM). However, these studies focus on the limited type of inclusions such as Al2 O3, SiO2, MgO, CaO, and MgAl2 O4 . To experimentally study the removability of various problematic inclusions that are not available in the market, optical floating zone and sintering techniques are presented here for the production of high purity micro‐particles. The syntheses of TiO2 and Al2 TiO5 inclusions are employed to demonstrate the advantages and potential of both techniques. These inclusions are then dissolved in the steelmaking slags using CSLM at 1430 °C. In situ observation shows that there is gas evolution during the reaction between slag and Al2 TiO5 particles prepared by both techniques. However, the gas evolution is more rapid during the dissolution of particles prepared by sintering and hinders in situ observations and measurements. The optical floating zone technique is capable of preparation of micro‐particles with high purity and less porosity. At 1430 °C, the Al2 TiO5 particles do not dissolve at all, whereas TiO2 particles completely dissolve in 200 s. Abstract : The current work presents the use of the optical floating zone method as a suitable technique for preparation of a wide range of simple and complex oxide type inclusions. The production of titanium oxide and aluminium titanate and their dissolution in slag using a high temperature laser scanning confocal microscope is presented.